The Effectiveness of Using Webtoon Applications in Teaching Reading Comprehension at The Eighth Grade of SMP Negeri 11 Mataram - Ghulam, Muhammad Thahirul; Nurtaat, H. Lalu; Lail, Husnul; Sujana, I Made (Jurnal Ilmiah Profesi Pendidikan, 2023)
Reading is an essential skill in the English language as it significantly impacts learning and facilitates the exploration of information. It enables us to acquire new knowledge, and broaden our perspectives, Grabe & Stoller (2013) contend that reading is a complex and dynamic process that involves considering, understanding, translating, analyzing, and discovering knowledge. Students often encounter multiple challenges when learning reading comprehension, such as limited vocabulary, inadequate time to comprehend the material, and disinterest in the teaching methods employed by educators, so this study aimed to investigate whether the use of a webtoon application as a medium has a significant effect on the achievement scores of second-grade students in literal reading comprehension. The research method used in this study is quantitative, and the researcher conducted a quasi-experimental study to investigate the impact of using Webtoon media in the teaching process. The treatment provided to the experimental group, which received instruction with the use of Webtoon media, while the control group did not receive any special treatment. The results of the study indicated that there was a noticeable difference in the pre-test and post-test scores, with an increase in the mean score from 60.46 to 73.86. Therefore, it was found that webtoon application is effective in teaching reading to improve reading skills, especially students' reading comprehension. The significant effect implies that when the material was presented through the Webtoon application, students became more engrossed in the content, leading to better comprehension of the text.